An empirical examination of factors contributing to the adoption of IFRS in developing countries - Aria Farah Mita; Nurul Husnah (Universitas Hayam Wuruk Perbanas, 2015)
This research aims to analyze factors that influence the likelihood of IFRS adoption in developing countries. Research that focuses on the IFRS adoption in developing countries is limited. Developing countries are supposed to get many benefits from the adoption of IFRS as it is a cheap shortcut to improve the quality of financial reporting to attract foreign capital and to finance its development. In addition to macroeconomic factors, this research also examines the influence of institutional factors and the development of local accounting standards. Using the binomial logit regression, the result shows that the regulatory quality of a country positively af-fects the possibility of IFRS adoption in developing countries. It means that the better quality of the regulator in those countries, the higher possibility to fully adopt the IFRS. Furthermore, there is a tendency that the countries will fully adopt the IFRS when they already have local accounting standards that previously referred to international standards. The results imply that the IASB strategy should focus more on cooperation with local regulators or groups of regional cooperation to reach its objective to develop single set of high quality international standard.